Green and intelligent: the role of AI in the climate transition - Nicholas Stern; Mattia Romani; Roberta Pierfederici; Manuel Braun; Daniel Barraclough; Shajeeshan Lingeswaran; Elizabeth Weirich-Benet; Niklas Niemann (npj Climate Action)
Abstract Artificial Intelligence (AI) can play a powerful role in supporting climate action while boosting sustainable and inclusive economic growth. However, limited research exists on the potential influence of AI on the low-carbon transition. Here we identify five areas through which AI can help build an effective response to climate threats. We estimate the potential for greenhouse gas (GHG) emissions reductions through AI applications in three key sectors—power, food, and mobility—which collectively contribute nearly half of global emissions. This is compared with the increase in data centre-related emissions generated by all AI-related activities.